THE ANALYSIS OF LEGAL PROTECTION FOR COPYRIGHT CREATORS TOWARD THE APPEARANCE OF SONGS COVERS CREATED BY OTHER MUSICIANS ON THE SOCIAL MEDIA PLATFORM TIKTOK - Hutabarat, Yolanda; Saragih, Ninda Elisa May Saputri; Silaban, Raynanda; Tambunan , Toman Sony (Lembaga Riset dan Pengembangan Sumatera Utara, 2025)
This legal writing aims to examine the legal protection of copyrighted song works performed by songwriters against the appearance of cover songs created by other musicians on the TikTok social media platform. This research is normative juridical with a statutory approach and case studies. The types and sources of data used include primary, secondary, and tertiary legal materials. Data collection techniques are carried out through library research, while data analysis uses the deduction method. The results showed that copyright legal protection of song works uploaded on the TikTok platform is often violated by parties without the right to cover songs. Songwriters are entitled to protection under Law Number 28 of 2014 concerning Copyright, specifically Article 9, Article 23, and Article 43 which regulates the moral and economic rights of creators. The case of song cover performances on TikTok shows the importance of supervision and more effective efforts to protect the copyright of song works. The results of this research are expected to provide legal guidance and policy recommendations for relevant parties, as well as encourage further discussions on copyright dynamics in the context of music performance in the digital era.